SIGHT TRANSLATION AND ITS STATUS IN THE TRAINING OF INTERPRETERS AND TRANSLATORS - Krapivkina, O. A. (Indonesian Journal of Applied Linguistics, 2018)
Sight translation has been considered as a supportive teaching method for simultaneous and consecutive interpretation for a long time and, due to recent developments in various fields such as business, law, science, and technology, it has gained more attention beyond simultaneous and consecutive interpretation. However, research on how sight translation is applied seems to be rare. This study, thus, aims to investigate the challenges and exercises to overcome them to improve student’s sight translation. This research employed a descriptive analysis using teacher’s assessment and students’ self-assessment questionnaire. There were 57 students in the final year at a university in Russia participating in the research. They were asked to conduct a sight translation of 248 words text. The finding shows that public speaking is the most challenging criteria for the students to achieve and the least challenging criteria are to deal with the register and genre convention. The article concludes that the following aspects of sight translation should become a training focus: clarity and fluency of delivery, the coherence of discourse, factual and linguistic accuracy, compliance with register and genre conventions, appropriate speaking speed rate, information timeliness, appropriate tone, volume, and voice projection. Some exercises in enhancing students’ sight translation are also provided. It is recommended that sight translation is taught to the students separately from other modes of interpreting because of different skills combination.